Evaluation of a dedicated ultrasound fine needle aspiration service for thyroid nodules. Issue 1 (28th January 2018) - Tan, Chelsea; Lavender, Ilona; Naismith, Amanda; Nguyen, Qui; Ptasznik, Ronnie; Nandurkar, Dee; Wong, Jennifer; Kumar, Beena; Fuller, Peter J.; Coombs, Peter R.; Mond, Michael
Abstract: Introduction: We studied whether: (1) a quality‐focused thyroid fine needle aspiration (FNA) service reduced the non‐diagnostic (ND) rate of FNA; (2) the implementation of thyroid FNA selection criteria resulted in higher proportion of Bethesda V and VI cytology and malignant histopathology; and (3) impact of radiologist's level of experience on ND rates. Method: The imaging and pathology computer databases were retrospectively searched for all patients who had thyroid FNAs at our hospitals from July 2004 to December 2016. Results: Three hundred thirty‐eight and 609 patients in pre‐thyroid and post‐thyroid service groups, respectively, were evaluated. The ND rate of 36.7% in pre‐thyroid service was significantly higher than post‐thyroid service at 14.6% ( p < 0.0001). The rates of Bethesda V and VI cytology in the pre‐thyroid service group did not differ significantly from the post‐thyroid group ( p = 0.266; p = 0.069). There was no significant difference in the histopathologic malignancy rates between the two groups ( p = 0.531). There was no significant difference in the ND rates of radiologists with varying experience ( p = 0.873). Discussion: On‐site cytology improved the ND rate of ultrasound‐guided thyroid FNA. Implementation of FNA selection criteria did not alter the rates of Bethesda V and VI cytology and malignant histopathology. The experience of radiologists did not significantly influence ND rates.